Single crystal elasticity of gold up to ∼20 GPa: Bulk modulus anomaly and implication for a primary pressure scale. (18th August 2017) - Yoneda, Akira; Fukui, Hiroshi; Gomi, Hitoshi; Kamada, Seiji; Xie, Longjian; Hirao, Naohisa; Uchiyama, Hiroshi; Tsutsui, Satoshi; Baron, Alfred Q. R.
Abstract: We measured the elasticity of single crystal gold (Au) and its lattice parameters under high pressure using inelastic X-ray scattering (IXS). The elastic moduli were obtained at five pressure points between 0 and 20 GPa. The pressure variation of the bulk modulus displays anomalous behavior, being nearly constant up to ∼5 GPa, and then steeply increasing at higher pressure. A similar anomaly is observed in first-principles calculations. An absolute pressure scale was derived by direct numerical integration of the bulk modulus over volume change. This yields a scale that gives slightly lower pressure values than those of previous work, about 5–10% lower at ∼20 GPa.